What’s the importance of portable tele-monitoring devices in patient therapeutic adherence? - Rodrigues, Orlando Pimenta (2017)
In the United Kingdom, it’s estimated that the National Health System spends every year almost $121 million in unused drugs. The hospital admission costs attributed to patients not taking their prescribed medicine properly was estimated to be between $44m and $240m per year. In the United States of America, medication non-adherence is estimated in $100 to $300 billions of avoidable healthcare costs annually, representing 3–10% of total United States healthcare costs. Studies show that improving medication adherence may have a greater influence on the health of the population than the discovery of any new therapy. Effective medicines are available for many conditions. Yet patients are non-adherent 50% of the time, reaching its critical point in certain disease states, such as asymptomatic conditions like hypertension, in which the incidence may approach 80%. Each disease has its special challenges. To answer the non-adherence problem, we must understand that people under certain disease states, are not aware of the danger when they unconsciously neglect the treatment and stop taking the prescribed medication. With the technological boom over the recent years, we were flooded with gadgets and devices that allow us to do practically everything in our everyday life, and the rise of tele-monitoring devices is going to be a reality, not only to monitor bio-signals but to help us with medication compliance. The objective of this dissertation is to gather information to establish what are the main strengths of nowadays technology to assemble the best integrated monitoring and control device, for therapeutic adherence. Our proposal is to create a therapeutic adherence monitoring device that consists in a smart blister coupled to a device which has the capacity to collect (from other medical devices) and send data (medicine taking time, blood pressure and oximetry) to a cloud every day. This allows the clinician to know, with high certain, if the patient is taking his medicine exactly how it has prescribed as well as the schedule of the same. Concluding, therapeutic non-adherence is a public health problem that leads to high economical and health losses. Nevertheless, we find that the technological devices fit within the lifestyle of the average person and present themselves as a solution.